Bibliometric Analysis of Research Dynamics of Circular Economy in Plastic Management - Judijanto, Loso; Firdayetti, Firdayetti (West Science Social and Humanities Studies, 2025)
The circular economy has emerged as a transformative approach to addressing the global plastic waste crisis by emphasizing resource recovery, recycling, and sustainability. This study presents a bibliometric analysis of research dynamics in circular economy and plastic management, utilizing data exclusively from the Scopus database and analyzed with VOSviewer. Key findings reveal significant growth in research activity over the past two decades, with central themes such as "circular economy," "waste management," and "plastic waste" dominating the field. The analysis identifies strong international collaborations, with countries like the United Kingdom, China, and India serving as key contributors. Emerging topics, including "pyrolysis" and "sustainable development," indicate a shift toward innovative technologies and broader sustainability goals. Despite advancements, gaps remain in understanding the socioeconomic implications of circular economy practices and consumer behavior's role in driving sustainability. This study provides critical insights into the research landscape, guiding future studies and policy frameworks toward effective and equitable plastic management solutions.